2009
DOI: 10.1007/s11211-009-0093-4
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Aspects of Justice in Relationships Between Consumers and Service Providers: A Confirmatory Factor Analysis

Abstract: There is a controversy in the justice literature as to whether interpersonal aspects of justice are best represented as one construct (interactional justice) or two (interpersonal justice and informational justice). Using confirmatory factor analysis, we tested competing models of these constructs on a sample of healthcare consumers (n = 1919) with respect to their justice judgments of primary care physicians. We found that the single factor model (interactional justice) represented a better fit to the data. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…1. Informational justice is excluded in this study because interpersonal relations comprise the core of IJ. In addition, Daly et al (2009), based on a large sample survey, found that the interpersonal aspect of organisational justice is best represented by one factor (interactional justice) instead of two factors (interpersonal and informational justice).…”
Section: Notesmentioning
confidence: 99%
“…1. Informational justice is excluded in this study because interpersonal relations comprise the core of IJ. In addition, Daly et al (2009), based on a large sample survey, found that the interpersonal aspect of organisational justice is best represented by one factor (interactional justice) instead of two factors (interpersonal and informational justice).…”
Section: Notesmentioning
confidence: 99%
“…摘 要 不同于"经济人"和"社会人"隐喻的公正研究,道德信念整合理论关注公正判断和公正动机的道德属 性,强调个体道德信念具有普世正当、非理智性、非他律性和非容忍性。该理论的核心观点包括道德价 值保护模型、权威独立假说、试金石假说和情绪假说。道德信念整合理论在解释利他性惩罚以及拒绝有 利不公正时有一定的理论优势,是"经济人"和"社会人"公正取向研究的有益补充。该理论整合了道 德发展与社会心理对公正的研究, 丰富了公正动机的研究并推动研究主体由当事人向第三方转换。 未来, 道德信念影响公正判断的机制以及不同取向公正动机如何权变的研究还需加强。 关键词 道德信念,独立权威假说,试金石假设,情绪假说 1. 引言 人们关心公正的动机是什么?影响公正判断的因素有哪些?二十世纪五十年代,基于"经济人"假 设的分配公平理论和相对剥夺理论认为,个体偏好追求自我利益的最大化,尤其是基本的物质需要受到 威胁以及将提高生产效率作为首要目标时,公正判断更依赖于主观的成本和利润分析。人们期望自己和 他人都遵守公平的规则,因为这是获得长期利益的最佳途径。"经济人"取向的公正研究依从于社会交 换理论,强调社会比较和主观价值感在公正判断中的作用,重视共享价值、权威序列、均衡匹配、互动 目标、资源形态等要素对公正判断的影响 (Tyler, 1997)。 二十世纪七十年代,随着程序公正研究的开展,从"经济人"假设中衍生出了"社会人"假设,该 取向主要从社会群体价值的视角来解读公正,强调公正是维护个体价值和自尊的重要途径,公正动机主 要源自社会认同、地位关注、相互依存等需要。在组织公正判断中,个体尤为关注程序的一贯性、无偏 性、正确性、修正性、代表性和伦理性 (Leventhal, Karuza, & Fry, 1980)。在人际交往中,互动公正 (international justice)最能代表公正的个体间方面,是公正当中最无形的成分,属于"无成本行为",交往 时的中立性、信赖性、地位尊重等互动变量会显著提高个体的公正感 (Daly, Williams, O'Connor, & Pouder, 2009)。 "经济人"和"社会人"假设引领公正动机研究取得了丰硕成果,但无论"经济人"还是"社会人" 假设,均认为公正动机和公正判断与资源分配及期待是否被满足有关 (Colquitt, Conlon, Wesson, & Porter, 2001)。最近"道德人"取向的研究则强调,把公正看成手段而不是目的其实忽略了公正的道德属性,纯 粹的公正关心受道德观念驱使,公正判断是根据内心的价值体系在道德框架内做出的,它更多地依存于 道德直觉而不是外部社会线索 (Rupp & Bell, 2010)。人们关心公正背后的动机是道德,而不仅仅是自我利 益和归属需要等非道德的动机。这符合进化心理学的观点,因为在进化心理学看来,那些学会在竞争和 合作中达到平衡的人发展出了道德善恶的概念,惩罚破坏契约和公正规范的人比那些没能发展出这些特 质的人有明显的适应优势 (Robinson, Kurzban, & Jones, 2007) 对于拒绝有利不公正倾向,道德信念整合理论认为,首先,应该明确区分结果公正和结果有利。基 于"经济人"和"社会人"假设的公正动机研究倾向把结果有利等同于结果公正,其公正判断主要基于 "满意/不满意"和"喜欢/不喜欢"等享乐性动机。拒绝有利不公正说明,结果公平比结果有利对公正判 断的影响更强烈,两者是明显不同的构建。其次,探讨个体如何界定"值得性"是说明公正动机的关键。 拒绝有利不公正反映了个体主要从道德的角度界定"值得性",而不是由"经济人"或"社会人"隐喻 的。再次,与"值得性"密切相关,社会比较是公正判断的核心概念,拒绝有利不公正反映了个体已经 将美德作为社会比较的角度,将道德认同看成最终的成功,而不是其他非道德因素 (Skitka, 2009)…”
Section: 收稿日期:2014年6月10日;修回日期:2014年6月16日;录用日期:2014年6月23日unclassified
“…2 There has been some debate within the literature that interactional justice is just one component of organizational justice instead of two (i.e., interpersonal and informational) subcomponents (Daly, Williams, O'Connor, & Pouder, 2009). For the sake of the present study, I will keep them separate as per Greenberg (1993), in order to fully understand the impact of different cultural self-construals on the perception of nepotistic social exchanges (warm treatment to family relation) and potentially unfair information distribution.…”
Section: Limitation Future Directions and Implicationsmentioning
confidence: 99%